Urbanisasi, Konsumsi Energi, dan Emisi CO2 : Adakah Perbedaan Korelasinya di Kawasan Barat Indonesia (KBI) dan Kawasan Timur Indonesia (KTI)? - Anastasia Widya Kristiani; Widyono Soetjipto (Department of Urban and Regional Planning, Diponegoro University, 2019)
Indonesia’s rapid urbanization has become one of the indicators of development that also continues to increase. It is undeniable, improving stage of development is often have an impact on environmental degradation such as excessive fossil energy consumption and CO2 emissions. However, not all regions in Indonesia are at the same stage of development. There are high economic and socio-demographic inequalities and differences between western Indonesia (KBI) and eastern Indonesia (KTI). This study aims to provide empirical evidence and analyze impact of urbanization on energy consumption and CO2 emissions in the country that has different stage of developments across the region. Taking regional heterogeneity in Indonesia, panel data estimation method was applied at the provincial level during the 2011-2015 period. The results of the study show that urbanization in KBI and KTI has different effects on per capita fossil energy consumption. Urbanization in KBI has a positive relationship to per capita energy consumption, whereas urbanization in the KTI has a negative correlation. Urbanization in KBI has a negative correlation with CO2 emissions. However, there was no difference effect of urbanization on CO2 emissions in both of region because the estimation results in KTI showed values that were not statistically significant. These findings not only help advance the existing literature, but also add insight to policy makers in the urban and regional planning.